An Intelligent Curriculum Management and Career Development Framework Integrating AI and Competency Standards in TVET - Nurtjahyadi Nurtjahyadi; Deviana Ridhani; Syahril Syahril; Sukardi Sukardi; Refdinal Refdinal; Rijal Abdullah; Elfi Tasrif (Postgraduate, University of Mataram, 2026)
The persistent misalignment between curriculum design, competency standards, and evolving industry requirements remains a critical challenge in Technical and Vocational Education and Training (TVET). Existing curriculum practices are largely static and insufficiently integrated with structured career pathways, resulting in skill mismatches and limited workforce readiness. This study proposes an intelligent curriculum management and career development framework integrating competency standards with AI-enabled decision support. A Design Science Research (DSR) methodology was employed through problem identification, framework design, demonstration, and evaluation. The framework was validated using a three-round Delphi study with TVET and curriculum experts and an empirical case study in an Indonesian TVET institution offering Information and Communication Technology (ICT) programmes based on curriculum documents and SKKNI competency standards. Performance was evaluated using alignment accuracy, relevance, and usability indicators. The results show that curriculum–competency alignment accuracy improved from **68.40%** to **91.20%**, while the framework identified four missing competencies and three redundant curriculum units. Career pathways aligned with industry roles achieved expert consensus exceeding **85.00%**. The proposed framework provides an adaptive, AI-enabled approach for data-driven curriculum governance, competency alignment, and career pathway planning, offering a replicable model for competency-based curriculum development in TVET